ASSESSMENT OF PHYTOCHEMICALS AND IN VITRO ANTIOXIDANT, ANTI-INFLAMMATORY ACTIVITY OF SARCOSTEMMA BRUNONIANUM WIGHT AND ARN - S., AMALA DIVYA; V., THAMARAIKANI; T., SEKAR (International Journal of Current Pharmaceutical Research, 2021)
Objective: Sarcostemma brunonianum Wight and Arn is a potential medicinal plant belonging to Asclepiadaceae. Bioactive constituents of the plant support the application of treating various ailments in the traditional system of medicine. The study aims to determine the presence of various phytoconstituents in stem, root, and flowers. Methods: Hot percolation method was carried out to obtain crude extracts using different solvent systems from low polar-high polar solvents ranging from petroleum ether, chloroform, (mid-polar) ethyl acetate, methanol and water. Estimation of total phenols, tannins and In vitro antioxidant, anti-inflammatory activities were evaluated for the determination of potential pharmaceutical drugs. Results: The results revealed the presence of some phytoconstituents such as phenols, tannins, glycosides, gums and mucilages. Ascorbic acid, BSA, Rutin and Gallic acid were used as the reference standard. The total phenolic content was found to be high in stem methanol extract 440.84±69.99 mg/g Gallic acid equivalent, whereas the tannin content was 291.78±4.68 mg/g GAE. The result proves that the S. brunonianum stem methanol extract possesses antioxidant and anti-inflammatory activities when compared to reference standards. In vitro, Nitric oxide scavenging activity of stem showed a maximum % of inhibition in methanol stem extract (24.39µg/ml) and anti-inflammatory activity maximum inhibition was found to be (55.56 %) in stem methanol and flower(53.62 %). The IC50 (concentration required for 50% inhibition) was also calculated for the DPPH radical model. Conclusion: This study results proclaims and justifies the role of folklore medicinal plant S. brunonianum in the treatment of inflammatory-related ailments and can be recommended for an effective drug.